SALVATION WITHOUT CULTIC MERIT: THE CHILD FIGURE IN MATTHEW 18-19 AS DECONSTRUCTION OF TEMPLE MERITOCRACY - Felicia Oetomo; Jonathan Octavianus (Jurnal Penelitian Progresif, 2026)
This study explores the significance of the "little child" figure in Matthew 18-19 as a radical soteriological statement that deconstructs the cultic meritocracy of the Temple. In first-century Judaism, although covenantal theology emphasized the grace of election, Temple practice had been corrupted into a system based on ritual and economic worthiness. Through socio-historical exegetical approaches and grammatical analysis, this study demonstrates that by placing the little child—a subject lacking both ritual and economic capacity—as the owner of the Kingdom of Heaven, Matthew performs a total subversion of the cultic hierarchy. Analysis of προσέφερον (prosepheron) and ἐπιθῇ τὰς χεῖρας (epithē tas cheiras) reveals Jesus as the new mediator who provides direct access without the mediation of the priestly system. The contrast with the rich man (Matt 19:16-30) reinforces that access to salvation does not depend on cultic performance or possession of wealth, but on radical dependence like that of a little child. These findings conclude that Matthew does not reject works, but rejects making cultic practices the exclusive basis for Kingdom access; the child figure shifts the locus of worthiness from ritual performance to a relationship of dependence on Christ as the sole mediator.